Degradable disulfide bond-containing peroxide ester initiator and application thereof in preparation of degradable branched polymer

By designing tert-butyl (isopropylbenzene) peroxide lipoate containing degradable disulfide bonds and peroxide ester bonds as initiators, a method of preparing degradable (super) branched polymers without additional branched monomers under conventional radical polymerization conditions is realized, and a high cost and uneven molecular weight distribution in the prior art is solved, and an efficient degradability efficiency and a simplified synthesis process is achieved.

CN119874666AActive Publication Date: 2025-04-25CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510120344.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-25
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The existing vinyl degradable branched polymer synthesis methods have problems such as high cost, harsh reaction conditions and uneven molecular weight distribution, making it difficult to achieve efficient degradation and large-scale application.

Method used

A new class of degradable initiator, tert-butyl lipoate peroxide (isopropylbenzene) ester, was designed to combine degradable disulfide bonds and peroxide ester bonds to be used in conventional radical polymerization, achieving a method of preparing degradable (super) branched polymers without the need for additional branched monomers.

Benefits of technology

This method simplifies the polymer synthesis process, reduces costs, improves product yield and purity, achieves efficient degradability efficiency, and has simple polymerization conditions and strong operability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to a peroxide ester initiator containing degradable disulfide bonds and application of the peroxide ester initiator to preparation of degradable branched polymers, and belongs to the field of functional initiator design. According to the preparation method, tert-butyl (cumene) hydrogen peroxide and lipoic acid are taken as raw materials, tert-butyl peroxide (cumene) lipoic acid ester containing disulfide bonds capable of being subjected to ring-opening polymerization is synthesized to serve as an initiator, vinyl monomers are initiated to be subjected to self-initiation free radical polymerization reaction, and the degradable branched polymer is successfully obtained. The peroxide ester functional initiator containing the degradable disulfide bond is synthesized by adjusting the amount-of-substance ratio of the initiator to the polymeric monomer and adjusting the branching degree of the polymer, and the degradable branched polymer is successfully prepared by the initiator under the conventional free radical polymerization condition without adding the branched monomer. The reaction method is simple and easy to implement, the monomer conversion rate is high, the branching degree of the polymer is controllable, and the branched polymer can be degraded and is high in applicability to synthesis of branched polymers from various types of monomers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a peroxyester initiator containing a degradable disulfide bond, a preparation method and an application in preparing a degradable branched polymer, and belongs to the field of organic synthesis and functional initiator design. Background Art

[0002] Due to its unique three-dimensional spherical structure, degradable (hyper) branched polymers have properties such as low viscosity, high solubility, high functionality, etc. The polymer is degradable and is believed to be widely used in polymer melt viscosity regulators, preparation of high solid content coatings and adhesives, drug carriers, catalysts, optoelectronics, new energy and many other fields. Its wide application prospects have attracted a large number of domestic and foreign experts and scholars to study and pay attention, becoming a hot research direction in polymer science.

[0003] At present, the main methods for synthesizing vinyl branched polymers include living polymerization, conventional free radical polymerization with chain transfer agents, etc. However, the reaction conditions of living polymerization are very harsh, the polymerization reaction cost is very high, and the types of monomers that can be adapted are limited. Compared with living polymerization, the reaction of conventional free radical polymerization is simple and easy, but the reported conventional free radical polymerization system has a complex composition and requires the addition of a large amount of control agent; the molecular weight of the synthesized degradable branched polymer is not high, and the molecular weight distribution is very wide; the branching point of the product is a chemical weak bond; the branching monomer itself is extremely unstable; the speed and degree of release of branching groups by potential branching monomers are restricted by many factors, etc. The degradation requirements are high, and it is difficult to achieve efficient degradation; vinyl polymers themselves are difficult to degrade, and cannot be degraded, recycled and reused, which is very harmful to the environment. These shortcomings have seriously restricted the theoretical research and large-scale application of vinyl degradable branched polymers.

[0004] The degradation of branched polymers, hyperbranched polymers, graft copolymers and reactive polymers has important theoretical and practical value in polymer science and engineering. It is of great significance to synthesize the above special structures and degradable polymers under simple conditions.

[0005] Pursuing the simplification and cheapness of the synthesis method is an important direction in the research of vinyl degradable branched polymers. Designing and synthesizing compounds containing degradable disulfide bonds and chemical weak bonds that can be homolytically cleaved at a suitable rate at conventional free radical polymerization reaction temperature (~80°C) to generate free radicals to initiate polymerization reactions will make the synthesis of the above-mentioned special structural degradable polymers extremely simple. To this end, we combined peroxyester bonds and lipoic acid disulfide bonds to synthesize a new type of degradable initiator: tert-butyl (isopropylphenyl) peroxy lipoate. Branched and hyperbranched polymers are a new type of initiator for conventional free radical polymerization and can be synthesized by self-initiated polymerization under conventional free radical polymerization conditions. Under appropriate conditions, macromolecular peroxides with peroxide side groups can also be synthesized. Polymers containing peroxyester bonds can not only initiate polymerization reactions under conventional free radical polymerization conditions to synthesize graft copolymers and comb polymers, but can also be used as reactive compatibilizers for polymer blends and polymer surface grafting modifications, while styrene and lipoic acid do not react. Summary of the invention

[0006] The invention discloses a peroxidized ester compound containing a degradable disulfide bond and a peroxide bond. The peroxidized ester compound containing a degradable disulfide bond and a peroxide bond can be used as a novel free radical polymerization initiator. Under conventional free radical polymerization conditions, a degradable (hyper) branched polymer is successfully prepared without adding a branching monomer. The novel free radical initiator of the invention contains both a degradable disulfide bond and a peroxide bond and has good storage stability. The method is simple and easy to synthesize a degradable (hyper) branched polymer, has strong operability, low production cost, and high product yield and purity.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The initiator is tert-butyl (isopropylbenzene) peroxide lipoic acid ester containing a degradable disulfide bond synthesized from a degradable disulfide bond and a peroxide, and the initiator structural formula is:

[0009]

[0010] Where R is -CH3 or

[0011] The preparation method of the above-mentioned peroxyester initiator containing degradable disulfide bonds is carried out according to the following steps:

[0012] (1) adding tert-butyl hydroperoxide or isopropylbenzene hydroperoxide, a catalyst and a dehydrating agent into a reaction vessel containing a solvent in a molar ratio of 1:0.1:0.11, wherein the mass of the solvent is 1 to 2 times the mass of the tert-butyl hydroperoxide or isopropylbenzene hydroperoxide, and uniformly stirring to form a mixed solution;

[0013] (2) gradually adding the mixed solution to the lipoic acid solution, wherein the amount of the lipoic acid substance is 1 to 1.5 times the amount of the tert-butyl hydroperoxide or isopropylbenzene hydroperoxide substance, and the reaction temperature is controlled at 15 to 30° C. After the addition is completed, continue stirring the reaction for 12 to 24 hours;

[0014] (3) After the reaction is stopped, the system is separated into layers and washed several times with saturated sodium bicarbonate and 10% hydrochloric acid aqueous solution, and then washed several times with a large amount of distilled water until neutral, and dried with an appropriate amount of anhydrous NaSO4, and the solvent is removed by rotary evaporation to obtain an initiator product.

[0015] Wherein, the solvent described in step (1) is dichloromethane, tetrahydrofuran or chloroform.

[0016] Wherein, the catalyst described in step (1) is 4-dimethylaminopyridine.

[0017] Wherein, the dehydrating agent in step (1) is N,N'-dicyclohexylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.

[0018] A method for preparing a degradable branched polymer is carried out according to the following steps: using a peroxide containing a degradable disulfide bond as an initiator and a vinyl monomer as a monomer to carry out self-initiated free radical polymerization, wherein the molar ratio of the initiator to the monomer is 1:50-200, the mass ratio of the solvent to the monomer is 0-4:1, the polymerization reaction temperature is controlled at 0-50°C, and the polymerization reaction time is controlled at 6-48 hours.

[0019] The solvent is dichloromethane, tetrahydrofuran or chloroform.

[0020] The vinyl monomer is styrene, methacrylic acid monomer, acrylic acid monomer, acrylic acid derivative or vinyl acetate monomer.

[0021] The polymerization system mentioned herein can be homopolymerization or copolymerization of vinyl monomers.

[0022] The polymerization method can be bulk polymerization, suspension polymerization, emulsion polymerization or solution polymerization, and the reaction is carried out under conventional polymerization conditions.

[0023] For example: dissolve the vinyl monomer and the peroxyester initiator containing a degradable disulfide bond in a reaction device, add a distilled water solution of sodium dodecyl sulfate after fully dissolving, stir thoroughly to a uniform light yellow emulsion (pre-emulsification), stir in an ice bath after pre-emulsification, vacuum to remove oxygen and fill with argon, add the reducing agent ferrous sulfate heptahydrate, the auxiliary reducing agent sodium formaldehyde sulfoxylate, and the chelating agent disodium ethylenediaminetetraacetic acid under argon atmosphere, and react in a constant temperature water bath at 25°C under oxygen-free conditions. After the reaction, a stable emulsion with a blue light is obtained. Take a certain amount of the emulsion, use toluene as an external standard, and use a saturated sodium chloride aqueous solution to break the emulsion. Extract the supernatant with n-hexane to determine the monomer conversion rate of 99%. The remaining sample is demulsified and precipitated in anhydrous ethanol, and the polymer product is repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer is repeatedly rinsed with anhydrous ethanol to remove the unreacted monomer. The ultra-high molecular weight copolymer finally obtained is placed in a vacuum oven and dried to constant weight to obtain a polymer with a branched structure.

[0024] Furthermore, the molar ratio of the vinyl monomer to ferrous sulfate heptahydrate, sodium formaldehyde sulfoxylate, and disodium ethylenediaminetetraacetate is 50-200: 0.01-0.1: 0.04-1: 0.02-0.5.

[0025] The invention has the advantages that the synthesized initiator raw material is easy to obtain and has good storage stability, the peroxide compound with a degradable disulfide bond is an initiator, which serves as both an initiator and a branching monomer, and has degradable performance, and does not need to be added with an additional initiator, and the branching monomer can be made to have a degradable group at the same time, and under conventional free radical polymerization conditions, no branching monomer needs to be added, and a degradable (hyper) branched polymer can be directly prepared. The branching degree and the degradability degree can be adjusted by adjusting the ratio of the initiator to the monomer, the polymerization reaction conditions are extremely simple, the operability is strong, the monomer conversion rate of the polymerization reaction is high, and the polymer degradability efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a high performance liquid chromatography (HPLC) spectrum of lipoic acid peroxide containing degradable disulfide bonds prepared in Example 1 of the present invention.

[0027] Figure 2 The NMR ( 1 H-NMR) spectrum.

[0028] Figure 3 This is the infrared (FT-IR) spectrum of the lipoic acid peroxide containing degradable disulfide bonds prepared in Example 1 of the present invention.

[0029] Figure 4 This is a Raman spectrum (Raman) diagram of lipoic acid peroxide containing degradable disulfide bonds prepared in Example 1 of the present invention.

[0030] Figure 5 This is a high performance liquid chromatography (HPLC) spectrum of lipoic acid peroxide containing degradable disulfide bonds prepared in Example 5 of the present invention.

[0031] Figure 6 The NMR ( 1 H-NMR) spectrum.

[0032] Figure 7 This is the infrared (FT-IR) spectrum of the lipoic acid peroxide containing degradable disulfide bonds prepared in Example 5 of the present invention.

[0033] Figure 8 It is the molecular weight distribution and Mark-Houwink curve diagram in Application Example 1.

[0034] Fig. 9 It is the molecular weight distribution and Mark-Houwink curve diagram in Application Examples 2 and 3.

[0035] Fig.10 These are the molecular weight distribution and Mark-Houwink curve diagrams of Application Examples 5, 6, and 7; and Comparative Example 1.

[0036] Fig.11 It is the molecular weight distribution and Mark-Houwink curve diagram in Application Example 9.

[0037] Fig.12 It is the molecular weight distribution and Mark-Houwink curve diagram in Application Example 10. DETAILED DESCRIPTION

[0038] The present invention uses the following embodiments to further illustrate the technical features of the present invention, but the protection scope of the present invention is not limited to the following embodiments.

[0039] Example 1

[0040] Dissolve lipoic acid (4.1264 g, 0.02 mol) and 4-dimethylaminopyridine (0.24434 g, 0.002 mol) in dichloromethane (DCM) (80 mL) and add tert-butyl hydroperoxide (1.8925 g, 0.021 mol), and control the temperature to 0-15°C. After the addition is complete, mix and stir to react for 30 minutes. Then drop N, N'-dicyclohexylcarbodiimide (4.3329 g, 0.021 mol) dissolved in dichloromethane (DCM) (10 mL), control the temperature to 0-15°C and mix for 30 minutes, then raise the reaction temperature to 15-30°C, and react for 12-20 hours. After the reaction is completed, the salt generated by the reaction is removed by suction filtration, and the mixture is washed with saturated sodium bicarbonate aqueous solution, 10% hydrochloric acid aqueous solution and distilled water until neutral. The oil phase is separated and dried with anhydrous sodium sulfate, and the product tert-butyl lipoyl peroxide is obtained by rotary evaporation. The total yield is 71.8% and the purity of the product is 97.8%. The product structural formula is:

[0041]

[0042] Tert-butyl lipoyl peroxide 1 H-NMR spectrum is shown in Figure 3 , where the peak with chemical shift δ=1.2~1.3 corresponds to the nine hydrogens on the tert-butyl group, the peak with chemical shift δ=1.4~3.2 corresponds to the hydrogens on all the methylene groups (—CH2), and the peak with chemical shift δ=3.5~3.6 corresponds to one hydrogen on the pentane ring.

[0043] Example 2

[0044] Dissolve lipoic acid (4.1264 g, 0.02 mol) and 4-dimethylaminopyridine (0.24434 g, 0.002 mol) in tetrahydrofuran (THF) (80 mL) and add tert-butyl hydroperoxide (1.8925 g, 0.021 mol), and control the temperature to 0-15°C. After the addition is complete, mix and stir to react for 30 minutes. Then drop N, N'-dicyclohexylcarbodiimide (4.3329 g, 0.021 mol) dissolved in ditetrahydrofuran (THF) (10 mL), control the temperature to 0-15°C and mix for 30 minutes, then raise the reaction temperature to 15-30°C, and react for 12-20 hours. After the reaction is completed, the salt generated by the reaction is removed by suction filtration, and the mixture is washed with saturated sodium bicarbonate aqueous solution, 10% hydrochloric acid aqueous solution and distilled water until neutral. The oil phase is separated and dried with anhydrous sodium sulfate, and the product tert-butyl lipoyl peroxide is obtained by rotary evaporation. The total yield is 80.5% and the purity of the product is 86.1%. The product structural formula is:

[0045]

[0046] Tert-butyl lipoyl peroxide 1In the H-NMR spectrum, the peak with a chemical shift of δ=1.2 to 1.3 corresponds to the nine hydrogen atoms on the tert-butyl group, the peak with a chemical shift of δ=1.4 to 3.2 corresponds to the hydrogen atoms on all the methylene groups (—CH2), and the peak with a chemical shift of δ=3.5 to 3.6 corresponds to one hydrogen atom on the pentyl ring.

[0047] Example 3

[0048] Dissolve lipoic acid (4.1264g, 0.02mol) and 4-dimethylaminopyridine (0.24434g, 0.002mol) in chloroform (TCM) (80mL) and add tert-butyl hydroperoxide (1.8925g, 0.021mol), and control the temperature to 0-15°C. After the addition is complete, mix and stir to react for 30min. Then drop N,N'-dicyclohexylcarbodiimide (4.3329g, 0.021mol) dissolved in chloroform (TCM) (10mL), control the temperature to 0-15°C and mix for 30min, then raise the reaction temperature to 15-30°C, and react for 12-20h. After the reaction is completed, the salt generated by the reaction is removed by suction filtration, and the mixture is washed with saturated sodium bicarbonate aqueous solution, 10% hydrochloric acid aqueous solution and distilled water until neutral. The oil phase is separated and dried with anhydrous sodium sulfate, and the product tert-butyl lipoyl peroxide is obtained by rotary evaporation. The total yield is 78.8% and the purity of the product is 80.6%. The product structural formula is:

[0049]

[0050] Tert-butyl lipoyl peroxide 1 In the H-NMR spectrum, the peak with a chemical shift of δ=1.2 to 1.3 corresponds to the nine hydrogen atoms on the tert-butyl group, the peak with a chemical shift of δ=1.4 to 3.2 corresponds to the hydrogen atoms on all the methylene groups (—CH2), and the peak with a chemical shift of δ=3.5 to 3.6 corresponds to one hydrogen atom on the pentyl ring.

[0051] Example 4

[0052] Dissolve lipoic acid (4.1264 g, 0.02 mol) and 4-dimethylaminopyridine (0.24434 g, 0.002 mol) in dichloromethane (DCM) (80 mL) and add tert-butyl hydroperoxide (1.8925 g, 0.021 mol), and control the temperature to 0-15°C. After the addition is complete, mix and stir to react for 30 minutes. Then drop 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (3.2601 g, 0.021 mol) dissolved in dichloromethane (DCM) (10 mL), control the temperature to 0-15°C and mix for 30 minutes, then raise the reaction temperature to 15-30°C, and react for 12-20 hours. After the reaction is completed, the salt generated by the reaction is removed by suction filtration, and the mixture is washed with saturated sodium bicarbonate aqueous solution, 10% hydrochloric acid aqueous solution and distilled water until neutral. The oil phase is separated and dried with anhydrous sodium sulfate, and the product tert-butyl lipoyl peroxide is obtained by rotary evaporation. The total yield is 81.8% and the purity of the product is 87.8%. The product structural formula is:

[0053]

[0054] Tert-butyl lipoyl peroxide 1 In the H-NMR spectrum, the peak with a chemical shift of δ=1.2 to 1.3 corresponds to the nine hydrogen atoms on the tert-butyl group, the peak with a chemical shift of δ=1.4 to 3.2 corresponds to the hydrogen atoms on all the methylene groups (—CH2), and the peak with a chemical shift of δ=3.5 to 3.6 corresponds to one hydrogen atom on the pentyl ring.

[0055] Example 5

[0056] Dissolve lipoic acid (4.1264 g, 0.02 mol) and 4-dimethylaminopyridine (0.24434 g, 0.002 mol) in dichloromethane (DCM) (80 mL) and add cumene hydroperoxide (1.8925 g, 0.021 mol), and control the temperature to 0-15°C. After the addition is complete, stir and react for 30 minutes. Then drop N, N'-dicyclohexylcarbodiimide (4.3329 g, 0.021 mol) dissolved in dichloromethane (DCM) (10 mL), control the temperature to 0-15°C and mix for 30 minutes, then raise the reaction temperature to 15-30°C, and react for 12-20 hours. After the reaction is completed, the salt generated by the reaction is removed by suction filtration, and the mixture is washed with saturated sodium bicarbonate aqueous solution, 10% hydrochloric acid aqueous solution and distilled water until neutral. The oil phase is separated and dried with anhydrous sodium sulfate, and the product is obtained by rotary evaporation, i-propyl thioctic acid peroxide, with a total yield of 75.1% and a purity of 94.8%. The product structural formula is:

[0057]

[0058] The chemical shift resonances of signals a and b at δ=7.50ppm and δ=7.25ppm are the 5 proton hydrogens on the phenyl group. The chemical shift resonances of signals c and c′ at δ=1.70ppm are the 6 proton hydrogens on the two -CH3 groups, and the chemical shift resonance of signal d at δ=1.85ppm is the 2 proton hydrogens on -CH2-. The chemical shift resonances of signals e, f and g at 1.59ppm are the 6 proton hydrogens on -CH2-. The chemical shift resonance of signal h at δ=3.49ppm is the one proton hydrogen on -CH-. The chemical shift resonances of signals i and j are the hydrogen atoms of -CH2-CH2- on the pentane ring.

[0059] Application Example 1: Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0060] Styrene (St 5.2018 g, 0.05 mol) and t-butyl peroxylipoate (prepared in Example 1) (0.0695 g, 0.25 mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601 g, 5% m.St) in distilled water (20.8072 g, 4 m.St) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath. Vacuum to remove oxygen and fill with argon, repeat 3 times, add reducing agent ferrous sulfate heptahydrate (FeSO4·7H2O0.0348g, 0.125mmol), auxiliary reducing agent sodium formaldehyde sulfoxylate (SFS0.0771g, 0.50mmol), chelating agent disodium ethylenediaminetetraacetate (EDTA-2Na0.0841g, 0.25mmol) under argon atmosphere, and react in a constant temperature water bath at 25℃ for 8h under oxygen-free condition. After the reaction, a stable emulsion with blue light is obtained. Take a certain amount of emulsion, use toluene as external standard, break the emulsion with saturated sodium chloride aqueous solution, extract the supernatant with n-hexane, and determine the monomer conversion rate to be 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol, and the polymer product was repeatedly washed with water to remove the emulsifier, and then the obtained polymer was repeatedly washed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-tert-butyl peroxythioate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =61000 g / mol, M w.MALLS =328000g / mol, molecular weight distribution is g′=0.522, proving that the obtained polymer has a branched structure.

[0061] Application Example 2 Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0062] Vinyl acetate (VA C4.2045g, 0.05mol) and tert-butyl lipoyl peroxide (0.0695g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, sodium dodecyl sulfate (0.2102g, 5% m.VA C ) of distilled water (16.8180 g, 4 m.VA C ) solution, fully stirred to a uniform light yellow emulsion (pre-emulsification), after the pre-emulsification is completed, stirred in an ice bath, vacuumed to remove oxygen and filled with argon, repeated 3 times, and then added with reducing agent ferrous sulfate heptahydrate (FeSO4·7H2O0.0139g, 0.05mmol), auxiliary reducing agent sodium formaldehyde sulfoxylate (SFS 0.0236g, 0.20mmol), chelating agent disodium ethylenediaminetetraacetic acid (EDTA-2Na0.0336g, 0.10mmol) in an argon atmosphere, and reacted in a constant temperature water bath at 25℃ under oxygen-free conditions for 24h. After the reaction, a stable emulsion with a blue glow was obtained. Take a certain amount of emulsion, use toluene as an external standard, break the emulsion with a saturated sodium chloride aqueous solution, extract the supernatant with n-hexane, and determine that the monomer conversion rate is 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol, and the polymer product was repeatedly washed with water to remove the emulsifier, and then the obtained polymer was repeatedly washed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-tert-butyl peroxy lipoic acid ester copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =61000 g / mol, M w.MALLS =93000g / mol, molecular weight distribution is g′=0.916, which proves that the obtained polymer has a branched structure.

[0063] Application Example 3 Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0064] Vinyl acetate (VA C 4.2045g, 0.05mol) and tert-butyl lipoyl peroxide (prepared in Example 1) (0.1390g, 0.50mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, sodium dodecyl sulfate (0.2102g, 5% m.VA C ) of distilled water (16.8180 g, 4 m.VA C) solution, fully stirred to a uniform light yellow emulsion (pre-emulsification), after the pre-emulsification is completed, stirred in an ice bath, vacuumed to remove oxygen and filled with argon, repeated 3 times, and then added with reducing agent ferrous sulfate heptahydrate (FeSO4·7H2O0.0139g, 0.05mmol), auxiliary reducing agent sodium formaldehyde sulfoxylate (SFS 0.0236g, 0.20mmol), chelating agent disodium ethylenediaminetetraacetic acid (EDTA-2Na0.0336g, 0.10mmol) in an argon atmosphere, and reacted in a constant temperature water bath at 25℃ under oxygen-free conditions for 24h. After the reaction, a stable emulsion with a blue glow was obtained. Take a certain amount of emulsion, use toluene as an external standard, break the emulsion with a saturated sodium chloride aqueous solution, extract the supernatant with n-hexane, and determine that the monomer conversion rate is 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol, and the polymer product was repeatedly washed with water to remove the emulsifier, and then the obtained polymer was repeatedly washed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-tert-butyl peroxythioate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =143000 g / mol, M w.MALLS =160000g / mol, molecular weight distribution is g′=0.878, which proves that the obtained polymer has a branched structure.

[0065] Application Example 4: Application of the above-mentioned lipoic acid cumyl ester initiator containing degradable disulfide bonds

[0066] Styrene (St 5.2018g, 0.05mol) and isopropyl thioperoxide (0.0886g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, the oxygen was removed by vacuum and argon was filled in. After repeating for 3 times, the reaction was placed in a 70°C constant temperature oil bath for 8h. The monomer conversion rate was measured by gas chromatography to be 92.6%. The obtained polymer was precipitated in ethanol and dried in a 30°C vacuum oven to constant weight to obtain a white solid powder. The molecular weight was measured to be M n.SEC =34000 g / mol, M w.MALLS =175000g / mol, molecular weight distribution is g′=0.732, proving that the obtained polymer has a branched structure.

[0067] Application Example 5

[0068] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042g, 0.025mol) and tert-butyl peroxy lipoate (0.0695g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601g, 5%M) in distilled water (20.8072g, 4M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath and vacuumed to remove oxygen and filled with argon. After repeating this for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O0.0348g, 0.125mmol), a co-reducing agent, formaldehyde and sodium bisulfate (SFS0.0771g, 0.50mmol), and a chelating agent, disodium ethylenediaminetetraacetate (EDTA-2Na0.0841g, 0.25mmol) were added under an argon atmosphere, and the mixture was reacted in a constant temperature water bath at 25°C under an anaerobic state for 8h. After the reaction, a stable emulsion with a blue glow was obtained. A certain amount of the emulsion was taken, and toluene was used as an external standard. A saturated sodium chloride aqueous solution was used to break the emulsion. The supernatant was extracted with n-hexane and the polymer styrene conversion rate was 99%, and the butyl acrylate conversion rate was 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol. The polymer product was repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer was repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =124000 g / mol, M w.MALLS =472000g / mol, molecular weight distribution is g'=0.990, which proves that the obtained polymer has a branched structure.

[0069] Application Example 6

[0070] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042 g, 0.025 mol) and tert-butyl peroxylipoate (0.0695 g, 0.25 mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601 g, 5% M) in distilled water (20.8072 g, 4 M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath, vacuumed to remove oxygen and filled with argon. After repeating this process for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O 0.0139 g, 0.05 mmol), an auxiliary reducing agent, formaldehyde and sodium bisulfate (SFS) were added in an argon atmosphere. 0.0336g, 0.20mmol), chelating agent disodium ethylenediaminetetraacetate (EDTA-2Na0.0841g, 0.10mmol), react in a constant temperature water bath at 25°C under oxygen-free conditions for 8h. After the reaction, a stable emulsion with a blue glow is obtained. A certain amount of the emulsion is taken, and toluene is used as an external standard. The emulsion is demulsified with a saturated sodium chloride aqueous solution, and the supernatant is extracted with n-hexane. The polymer styrene conversion rate is 99%, and the butyl acrylate conversion rate is 99%. The remaining sample is demulsified and precipitated in anhydrous ethanol, and the polymerization product is repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer is repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer finally obtained is placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =162000 g / mol, M w.MALLS =781000g / mol, molecular weight distribution is g′=0.970, which proves that the obtained polymer has a branched structure.

[0071] Application Example 7

[0072] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042g, 0.025mol) and tert-butyl peroxy lipoate (0.0695g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601g, 5%M) in distilled water (20.8072g, 4M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath and vacuumed to remove oxygen and filled with argon. After repeating this for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O0.0014g, 0.005mmol), a co-reducing agent, formaldehyde and sodium bisulfate (SFS0.0024g, 0.02mmol), and a chelating agent, disodium ethylenediaminetetraacetate (EDTA-2Na0.0034g, 0.01mmol) were added under an argon atmosphere, and the mixture was reacted in a constant temperature water bath at 25°C under an anaerobic state for 24h. After the reaction, a stable emulsion with a blue glow was obtained. A certain amount of the emulsion was taken, and toluene was used as an external standard. A saturated sodium chloride aqueous solution was used to break the emulsion. The supernatant was extracted with n-hexane and the polymer styrene conversion rate was 99%, and the butyl acrylate conversion rate was 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol. The polymer product was repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer was repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =273000 g / mol, M w.MALLS =1023000g / mol, molecular weight distribution is g′=0.906, which proves that the obtained polymer has a branched structure.

[0073] Application Example 8 Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0074] Acrylonitrile (AN 1.3266 g, 0.025 mol), isooctyl acrylate (2-EHA 4.6070 g, 0.025 mol) and tert-butyl peroxy thioctate (0.0695 g, 0.25 mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601 g, 5% M) in distilled water (20.8072 g, 4 M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath, vacuumed to remove oxygen and filled with argon. After repeating this process for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O 0.0348 g, 0.125 mmol), an auxiliary reducing agent, sodium formaldehyde sulfoxylate (SFS) were added in an argon atmosphere. 0.0771g, 0.50mmol), chelating agent disodium ethylenediaminetetraacetate (EDTA-2Na0.0841g, 0.25mmol), react in a constant temperature water bath at 25°C under oxygen-free conditions for 8h. After the reaction, a stable emulsion with a blue glow is obtained. A certain amount of the emulsion is taken, and toluene is used as an external standard. A saturated sodium chloride aqueous solution is used to break the emulsion, and the supernatant is extracted with n-hexane to determine the polymer acrylonitrile conversion rate of 99%, and the acrylate iso-octyl ester conversion rate of 99%. The remaining sample is demulsified and precipitated in anhydrous ethanol, and the polymerization product is repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer is repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight acrylonitrile-co-acrylate is finally obtained. The copolymer is placed in a vacuum oven at 30°C and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =233000 g / mol, M w.MALLS =361000g / mol, molecular weight distribution is

[0075] Application Example 9 Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0076] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042g, 0.025mol) and tert-butyl peroxy lipoate (0.0695g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601g, 5%M) in distilled water (20.8072g, 4M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath and vacuumed to remove oxygen and filled with argon. After repeating this for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O0.0014g, 0.005mmol), a co-reducing agent, sodium formaldehyde sulfoxylate (SFS0.0024g, 0.02mmol), and a chelating agent, disodium ethylenediaminetetraacetate (EDTA-2Na0.0034g, 0.01mmol) were added under an argon atmosphere, and the mixture was reacted in a constant temperature water bath at 25°C under an anaerobic state for 24h. After the reaction, a stable emulsion with a blue glow was obtained. A certain amount of the emulsion was taken, and toluene was used as an external standard. A saturated sodium chloride aqueous solution was used to break the emulsion. The supernatant was extracted with n-hexane and the polymer styrene conversion rate was 99%, and the butyl acrylate conversion rate was 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol. The polymer product was repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer was repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =273000 g / mol, M w.MALLS =1023000g / mol, molecular weight distribution is It is proved that the obtained polymer has a branched structure. Stir polystyrene-co-butyl acrylate (0.05g) and dioxane (5.00g) at an appropriate speed for a period of time until they are fully dissolved, then add dithiothreitol (0.01g), stir until dissolved, seal and react in a 30°C constant temperature oil bath for a certain period of time. The reaction liquid is a turbid yellow liquid with yellow solid precipitation. After the reaction is completed, the sample is passed through a neutral alumina column and precipitated in anhydrous ethanol. Finally, the degraded polymer is placed in a 30°C vacuum oven and dried to constant weight. The molecular weight of the obtained polymer after degradation is Mn.SEC=251000g / mol, Mw.MALLS=742000g / mol, and the molecular weight distribution is g′=1.000, the molecular weight of the obtained polymer after degradation is greatly reduced. Fig.11 shown.

[0077] Application Example 10 Application of the above-mentioned tert-butyl peroxide initiator containing degradable disulfide bonds

[0078] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042 g, 0.025 mol) and tert-butyl peroxylipoate (0.4170 g, 1.50 mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601 g, 5% M) in distilled water (20.8072 g, 4 M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath, vacuumed to remove oxygen and filled with argon. After repeating this process for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O 0.0014 g, 0.005 mmol), an auxiliary reducing agent, sodium formaldehyde sulfoxylate (SFS) were added in an argon atmosphere. 0.0024g, 0.02mmol), chelating agent disodium ethylenediaminetetraacetate (EDTA-2Na0.0034g, 0.01mmol), react in a constant temperature water bath at 25°C under oxygen-free conditions for 24 hours. After the reaction, a stable emulsion with a blue glow is obtained. Take a certain amount of the emulsion, use toluene as an external standard, and use a saturated sodium chloride aqueous solution to break the emulsion. The supernatant is extracted with n-hexane to determine the polymer styrene conversion rate of 99%, and the butyl acrylate conversion rate of 99%. The remaining sample is demulsified and precipitated in anhydrous ethanol, the polymerization product is repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer is repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer finally obtained is placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene-co-butyl acrylate containing a disulfide bond in the main chain is M n.SEC =259000 g / mol, M w.MALLS =1074000g / mol, molecular weight distribution is g′=0.870, which proves that the obtained polymer has a branched structure. Stir polystyrene-co-butyl acrylate (0.05g) and dioxane (5.00g) at an appropriate speed for a period of time until they are fully dissolved, then add dithiothreitol (0.01g), stir until dissolved, seal and react in a 30℃ constant temperature oil bath for a certain period of time. The reaction liquid is a turbid yellow liquid with yellow solid precipitation. After the reaction is completed, the sample is passed through a neutral alumina column and precipitated in anhydrous ethanol. Finally, the degraded polymer is placed in a 30℃ vacuum oven and dried to constant weight. The molecular weight of the obtained polymer after degradation is M n.SEC =79000 g / mol, M w.MALLS =253000g / mol, molecular weight distribution is g′=1.000. The molecular weight of the obtained polymers after degradation is greatly reduced. Fig.12 shown.

[0079] Comparative Example 1

[0080] Styrene (St 2.6038 g, 0.025 mol), butyl acrylate (n-BA 3.2042g, 0.025mol) and tert-butyl hydroperoxide (0.0225g, 0.25mmol) were dissolved in a Schlenk single-mouth reaction bottle. After being fully dissolved, a solution of sodium dodecyl sulfate (0.2601g, 5%M) in distilled water (20.8072g, 4M) was added and stirred until a uniform light yellow emulsion (pre-emulsification) was obtained. After the pre-emulsification was completed, the mixture was stirred in an ice bath, vacuumed to remove oxygen and filled with argon. After repeating this for 3 times, a reducing agent, ferrous sulfate heptahydrate (FeSO4·7H2O0.0014g, 0.005mmol), a co-reducing agent, sodium formaldehyde sulfoxylate (SFS0.0024g, 0.02mmol), and a chelating agent, disodium ethylenediaminetetraacetate (EDTA-2Na0.0034g, 0.01mmol) were added under argon atmosphere, and the mixture was reacted in a constant temperature water bath at 25°C under anaerobic conditions for 24h. After the reaction, a stable emulsion with a blue glow was obtained. A certain amount of the emulsion was taken, and toluene was used as an external standard. A saturated sodium chloride aqueous solution was used to break the emulsion. The supernatant was extracted with n-hexane and the polymer styrene conversion rate was 99%, and the butyl acrylate conversion rate was 99%. The remaining sample was demulsified and precipitated in anhydrous ethanol. The polymer product was repeatedly rinsed with water to remove the emulsifier, and then the obtained polymer was repeatedly rinsed with anhydrous ethanol to remove the unreacted monomers. The ultra-high molecular weight styrene-co-butyl acrylate copolymer was finally placed in a 30°C vacuum oven and dried to constant weight to obtain a white solid powder. The molecular weight of the obtained branched polystyrene containing disulfide bonds in the main chain is M n.SEC =104000 g / mol, M w.MALLS =323000g / mol, molecular weight distribution is The molecular weight distribution is unimodal and symmetrical, proving that the polymer has an unbranched structure. Fig.10 shown.

[0081] Polystyrene-co-butyl acrylate (0.05g) and dioxane (5.00g) were stirred at an appropriate speed for a period of time until they were fully dissolved, and then dithiothreitol (0.01g) was added and stirred until dissolved. After sealing, the mixture was reacted in a 30°C constant temperature oil bath for a certain period of time. The reaction liquid was a turbid yellow liquid with yellow solid precipitation. After the reaction, the sample was passed through a neutral alumina column and precipitated in anhydrous ethanol. Finally, the degraded polymer was placed in a 30°C vacuum oven and dried to constant weight. The molecular weight of the obtained polymer did not change, proving that it could not be degraded.

[0082] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A peroxyester initiator containing a degradable disulfide bond, characterized in that: The structural formula of the initiator is: Where R is -CH3 or 2. The use of the peroxyester initiator containing a degradable disulfide bond in the preparation of a degradable branched polymer according to claim 1, characterized in that: A peroxyester initiator containing a degradable disulfide bond and a vinyl monomer are used as monomers to initiate a free radical polymerization reaction in a solvent to synthesize a degradable branched polymer.

3. The use of a peroxyester initiator containing a degradable disulfide bond in preparing a degradable branched polymer according to claim 2, characterized in that: The molar ratio of the initiator to the vinyl monomer is 1:50-200, and the mass ratio of the solvent to the monomer is 0-4:

1.

4. The use of the peroxyester initiator containing a degradable disulfide bond in the preparation of a degradable branched polymer according to claim 2, characterized in that: The polymerization reaction temperature is controlled at 0-50° C., and the polymerization reaction time is controlled at 6-48 hours.

5. The use of the peroxyester initiator containing a degradable disulfide bond in the preparation of a degradable branched polymer according to claim 2, characterized in that: The solvent is dichloromethane, tetrahydrofuran or chloroform.

6. The use of the peroxyester initiator containing a degradable disulfide bond in the preparation of a degradable branched polymer according to claim 2, characterized in that: The vinyl monomer is styrene, methacrylic acid monomer, acrylic acid monomer, acrylic acid derivative or vinyl acetate monomer.

7. The use of the peroxyester initiator containing a degradable disulfide bond in the preparation of a degradable branched polymer according to claim 2, characterized in that: The polymerization reaction system is the homopolymerization or copolymerization of vinyl monomers.

Citation Information

Patent Citations

  • Peroxidation ester initiator containing polymerizable double bond and preparation method

    CN102584664A

  • Method for preparing branched polymer

    CN102675492A

  • O-dithialane-photosensitive compositions

    US3801327A